Current status and comparison of personal characteristics of freshmen undergraduates majoring in clinical pharmacy in southwest China - Liu, Yang; Zheng, Hang; Jiang, Junhao; Yan, Bo (Frontiers in Medicine, 2025)
ObjectiveWe aimed to analyze and compare the personal characteristics of undergraduate freshmen enrolled in clinical pharmacy across colleges and universities in southwest China. The goal was to delineate the current composition of the freshmen cohort and offer insights for targeted teaching strategies.MethodsFrom January 2024 to February 2024, a questionnaire survey was conducted among first-year undergraduate students majoring in clinical pharmacy in eight universities in the Sichuan Province, Yunnan Province, Guizhou Province, and Chongqing City, China. The survey covered basic information and various scales.ResultsOverall, 535 first-year undergraduate students, majoring in clinical pharmacy, completed the survey. Significant regional differences in personal characteristics existed (p < 0.05). While the respondents had similar personality traits, differences existed in their achievement goals, motivations, interests, and expectations (p < 0.05).ConclusionThis study provides suggestions for optimizing training programs to improve the education quality in clinical pharmacy, students’ practical abilities, and career expectations. Moreover, it offers valuable insights for refining training strategies and educational practices in clinical pharmacy, laying a solid foundation for the cultivation of future professional personnel.